Decoupling Proton and Cation Contributions to Capacitive Charge Storage in Birnessite in Aqueous Electrolytes. Issue 22 (24th November 2021) - Saeed, Saeed; Fortunato, Jenelle; Ganeshan, Karthik; van Duin, Adri C. T.; Augustyn, Veronica
Abstract: Nanostructured birnessite is of interest as an electrode material for aqueous high power electrochemical energy storage as well as desalination devices. In neutral pH aqueous electrolytes, birnessite exhibits a capacitive response attributed to the adsorption of cations and protons at the outer surface and within the hydrated interlayer. Here, we utilize the understanding of proton‐coupled electron transfer (PCET) in buffered electrolytes to decouple the role of protons and cations in the capacitive charge storage mechanism of birnessite at neutral pH. We find that without buffer, birnessite exhibits primarily potential‐independent (capacitive) behavior with excellent cycling stability. Upon the addition of buffer, the capacity initially increases and the cyclic voltammograms become more potential‐dependent, features attributed to the presence of PCET with the birnessite. However, long‐term cycling in the buffered electrolyte leads to significant capacity fade and dissolution, which is corroborated through ex situ characterization. ReaxFF atomistic scale simulations support the observations that proton adsorption leads to birnessite degradation and that capacitive charge storage in birnessite is primarily attributed to cation adsorption at the outer surface and within the interlayer. Abstract : Contribution of cations and protons to capacitive charge storage in birnessite is decoupled using buffered electrolytes. We find cations to be the primary species associated with capacitive storage, whereas protons lead to PCET‐driven dissolution of birnessite.